Hyperthermic intraperitoneal chemotherapy (HIPEC) in combined treatment of locally advanced and intraperitonealy disseminated gastric cancer: A retrospective cooperative Central‐Eastern European study. (29th April 2019) - Yarema, Roman; Mielko, Jerzy; Fetsych, Taras; Ohorchak, Myron; Skorzewska, Magdalena; Rawicz‐Pruszyński, Karol; Mashukov, Artem; Maksimovsky, Viatcheslav; Jastrzębski, Tomasz; Polkowski, Wojciech; Gyrya, Petro; Kovalchuk, Yuriy; et al.
Abstract: Background and Objectives: Clinical experience in Western Europe suggests that cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) are promising methods in the management of gastric cancer (GC) with peritoneal metastases. However, there are almost no data on such treatment results in patient from Central‐Eastern European population. Methods: A retrospective cooperative study was performed at 6 Central‐Eastern European HIPEC centers. HIPEC was used in 117 patients for the following indications: treatment of GC with limited overt peritoneal metastases (n = 70), adjuvant setting after radical gastrectomy (n = 37) and palliative approach for elimination of severe ascites without gastrectomy (n = 10). Results: Postoperative morbidity and mortality rates were 29.1% and 5.1%, respectively. Median overall survival in the groups with therapeutic, adjuvant, and palliative indications was 12.6, 34, and 3.5 months. The only long‐term survivors occurred in the group with peritoneal cancer index (PCI) of 0‐6 points without survival difference in groups with PCI 7‐12 vs PCI 13 or more points. Conclusions: GC patients with limited peritoneal metastases can benefit from CRS + HIPEC. Hyperthermic intraperitoneal chemotherapy could be an effective method of adjuvant treatment of GC with a high risk of intraperitoneal progression. No long‐term survival may be expected after palliative approach to HIPEC. Abstract : This study shows that gastric cancer patients with limited peritoneal metastases can benefit from cytoreductive surgery and HIPEC. HIPEC could be an effective method of adjuvant treatment of gastric cancer with a high risk of intraperitoneal progression.